Myth and Migration:: Unpicking the Career of the Reverend John Sprott - Murison, Barbara (Acadiensis, 2009)
Abstract The Scots appear to possess a particular flair for the creation, transmission, and mutation of myths, and while modern scholars have attempted to deconstruct such myths it is clear that they have been of substantial importance in the making of local and national identities. This article uses one Scottish emigrant to Nova Scotia as a test case. It unpicks the Galloway background of the Reverend John Sprott’s first four decades and the assembling of his cultural baggage, and it follows him for 50 years in his adopted homeland. A map of his mental journeyings is the result.